2018
DOI: 10.1083/jcb.201711104
|View full text |Cite
|
Sign up to set email alerts
|

Actin filaments partition primary cilia membranes into distinct fluid corrals

Abstract: Physical properties of primary cilia membranes in living cells were examined using two independent, high-spatiotemporal-resolution approaches: fast tracking of single quantum dot-labeled G protein-coupled receptors and a novel two-photon super-resolution fluorescence recovery after photobleaching of protein ensemble. Both approaches demonstrated the cilium membrane to be partitioned into corralled domains spanning 274 ± 20 nm, within which the receptors are transiently confined for 0.71 ± 0.09 s. The mean memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 79 publications
1
42
0
Order By: Relevance
“…Thus, prom-containing membrane microdomains may act as building units that elaborate and/or maintain the proper composition of microvillar and ciliary membranes and thus influence interactions with cytoplasmic regulatory proteins. They could also affect membrane fluidity by creating distinct liquid phases, and hence, influence the diffusion of their constituents (74). The uneven distribution of PROM1 (or prom3) observed in cilia of wild-type PROM1 (or prom3-HA) + cells compared to its uniform spread in mutated PROM1 + cells suggests the disruption of these membrane microdomains (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, prom-containing membrane microdomains may act as building units that elaborate and/or maintain the proper composition of microvillar and ciliary membranes and thus influence interactions with cytoplasmic regulatory proteins. They could also affect membrane fluidity by creating distinct liquid phases, and hence, influence the diffusion of their constituents (74). The uneven distribution of PROM1 (or prom3) observed in cilia of wild-type PROM1 (or prom3-HA) + cells compared to its uniform spread in mutated PROM1 + cells suggests the disruption of these membrane microdomains (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the morphological disturbance of primary cilia observed upon overexpression of mutants Y819/828F may also reflect a disrupted interaction of proms with cholesterol-and/or ganglioside-rich membrane microdomains (21,26,30,31) as suggested for the altered microvillar structure (28). The local activity of PI3K that converts PIP2 into PIP3 in the inner leaflet of the plasma membrane can regulate the interaction of the lipid bilayer with the underlying structural core of cellular protrusions and/or the transport of membrane components therein (28,(70)(71)(72)(73)(74). The accumulation of Arl13b at the ciliary base of cells expressing the PROM1 mutant may result from a defect in the aforementioned mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies provided indirect and contradictory pieces of evidence regarding the presence of f-actin inside primary cilia 17,18,55 . Traces of actin-related proteins such as Arpc3 17 , the inverted formin FHDC1 56 , myosin 17 , microtubule-actin crosslinking factors 18 and other actin interacting proteins 55,57 have been found.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies provided indirect and contradictory pieces of evidence regarding the presence of f-actin inside primary cilia 17,18,55 . Traces of actin-related proteins such as Arpc3 17 , the inverted formin FHDC1 56 , myosin 17 , microtubule-actin crosslinking factors 18 and other actin interacting proteins 55,57 have been found. Recently, actin has been shown to form puncta at ciliary excision sites 58 and has been linked to ciliary exocytic vesicle formation 59 and cilia decapitation 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we observed an increase in CHMP4B immunoreactivity in cells treated with cyto D ( Figure 7B). 47 Therefore, it is likely that the entry of CHMP4B into cilia and its distribution within cilia may be limited by F-actin. A recent study showed that the ciliary membrane is partitioned into nanodomains that are F I G U R E 6 CHMP4B plays a role in maintaining the structural integrity of cilia.…”
Section: Actin Depolymerization Rescues Loss Of Cilia In Chmp4b-depmentioning
confidence: 99%